2019
DOI: 10.3389/fmicb.2019.02118
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Distinct Skin and Gut Microbiomes of the Northern Pike (Esox lucius)

Abstract: The microbiome of freshwater fish has important implications for both commercial and recreational fishing because it can have significant impacts on host heath, spoilage rates, and susceptibility to disease. The aqueous environment serves as a possible avenue for continuous introduction of microbes to an animal host, but little is known about how the surrounding microbiota contribute to piscine microbiomes. To better understand the composition of the fish microbiome exposed to the natural environment, we profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 92 publications
(127 reference statements)
4
27
0
Order By: Relevance
“…Regardless of the diet type, marked differences in terms of alpha diversity were found between gut and skin microbiota, being the latter characterized by higher microbial diversity and richness. Previous studies on trout and other fresh water species displayed a similar trend with a lower alpha diversity in the gut than in the skin mucosal surface [22,41,42]. Unfortunately, in contrast to high number of studies focused on sh gut microbiome, the skin mucus microbiome remains largely underexplored.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Regardless of the diet type, marked differences in terms of alpha diversity were found between gut and skin microbiota, being the latter characterized by higher microbial diversity and richness. Previous studies on trout and other fresh water species displayed a similar trend with a lower alpha diversity in the gut than in the skin mucosal surface [22,41,42]. Unfortunately, in contrast to high number of studies focused on sh gut microbiome, the skin mucus microbiome remains largely underexplored.…”
Section: Discussionmentioning
confidence: 91%
“…Initially, sh skin is colonized by bacteria present in the water, but over time, the super cial mucus harbors an increasingly divergent microbial community [41,43]. Like in intestine, the balance between members of skin microbial community, i.e., commensals, symbionts or pathogenic bacterial strains, collectively forming skin microbiome, is important to preserve sh health.…”
Section: Discussionmentioning
confidence: 99%
“…The water microbiome of shponds were signi cantly distinct and more diverse than the skin and gill microbiomes of both sh, regardless of their age. It is known that free-living microbial communities retain higher richness than host-associated communities [31], with many studies showing a higher bacterial diversity in water relative to sh skin [28,30,36,[58][59][60], gills [14,36], gut [7,15,18,21,61], stomach [36], hindgut [36] and whole larvae [22]. Although some studies in sh have shown that the microbial communities found in the water tend to be recovered in the larval gut microbiome [17,21], others have also shown that water microbiomes do not in uence directly the microbiomes of sh mucosa [7, 8, 13-15, 18, 19, 22, 28, 30, 34, 36, 58-60, 62, 63].…”
Section: Fish and Water Microbiome Comparisonsmentioning
confidence: 99%
“…Previous sh studies of skin and gill microbiomes [e.g. 7,8,36,61], including seabass and seabream [71], have shown remarkable differences in microbial composition and structure across host species and tissues. Additionally, a previous study by our group [72] showed that disease and antibiotic treatment in seabass leads to asymmetrical shifts in skin and gill microbial communities.…”
Section: Data Processing and Statistical Analysismentioning
confidence: 99%
“…The water microbiota of shponds were signi cantly distinct and more diverse than the skin and gill microbiota of both sh, regardless of their age. It is known that free-living microbial communities retain higher richness than host-associated communities [31], with many studies showing a higher bacterial diversity in water relative to sh skin [28,30,36,[66][67][68], gills [14,36], gut [7,15,18,21,69], stomach [36], hindgut [36] and whole larvae [22]. Although some studies in sh have shown that the microbial communities found in the water tend to be recovered in the larval gut microbiota [17,21], others have also shown that water microbiota do not in uence directly the microbiota of sh mucosa [7, 8, 13-15, 18, 19, 22, 28, 30, 34, 36, 66-68, 70, 71].…”
Section: Fish and Water Microbiota Comparisonsmentioning
confidence: 99%